Closing the mental health treatment gap through the collaboration of traditional and Western medicine in Liberia. Issue 4 (2nd October 2018) - Herman, Augusta R.; Pullen, Samuel J.; Lange, Brittany C. L.; Christian-Brathwaite, Nicole; Ulloa, Melissa; Kempeh, Michael; Karnga, Dyujay; Johnson, Dorothy; Harris, Benjamin; Henderson, David C.; Borba, Christina P. C.
ABSTRACT: Liberians have experienced significant psychological trauma following fourteen years of violent civil war and the 2014–2015 Ebola epidemic, but there are only two psychiatrists for the entire population. However, many traditional healers commonly treat mental health-related illnesses throughout the country. This paper examines the potential for collaboration between traditional and Western medicine to close the mental health treatment gap in Liberia. We conducted 35 semi-structured qualitative interviews with Liberian traditional healers and utilizers of traditional medicine asking questions about common health problems, treatments, beliefs, and personal preferences. Participants discussed cultural attitudes, beliefs, and structural factors that may influence collaboration between traditional and Western medicine. Healers expressed willingness to collaborate in order to strengthen their skills, though realized Western physicians were hesitant to collaborate. Additionally, Liberians believed in both medical traditions, though preferred Western medicine. Finally, structural factors such as geographic distance and financial barriers made traditional medicine more accessible than Western medicine. Traditional healers and utilizers support collaboration as evidenced by their perceptions of cultural attitudes, beliefs, and structural factors within the Liberian context. With Liberia's overwhelming mental illness burden, a collaboration between traditional healers and Western medicine physicians offers a solution to the treatment gap in Liberian mental health care.